Ideologi Surat Kabar dalam Pemberitaan Terorisme - Fajar Syuderajat (Fakultas Dakwah dan Komunikasi UIN Sunan Gunung Djati Bandung Sunan Gunung Djati Bandung, 2017)
This paper this study was to determine the ideology of Newspaper Coverage Off Execution Amrozy Cs. on Newspaper Kompas and Republika. The method used in this research is the analysis method semiotics model of Ferdinand de Saussure with a qualitative approach. The results showed that: (a) Option speech text, as well as the news angle images of photographs or illustrations that reproduce the graph becomes a news event is strongly influenced by the ideology of the media is concerned. (B) Compass showing partiality to the international agenda by using the term